THE ROLE OF LEADERSHIP IN IMPROVING THE QUALITY OF HUMAN RESOURCES IN MADRASAH - Marliani, Lina; Rosyada, Dede; Salam, Abdus; Meliani, Fitri (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study aimed to examine how the head of MI Ma'arif Kedawung, uses his leadership style to improve the effectiveness of teacher performance. The achievement of quality education goals is highly dependent on teacher performance. Field studies with other qualitative methods were used to compile this research. In-depth interviews, participant observation, and document analysis were used to collect this data. This study's subjects were the madrasah's head and two educators of MI Ma'arif Kedawung. Our purpose in conducting this research is to gain insight into how the leadership style of madrasah heads builds a conducive environment that supports the formation of quality human resources in the world. The research results on the leadership style of the head of the madrasah influence the performance of teachers in MI Ma'arif Kedawung. The results of this study show democratic leadership styles have a positive impact on encouraging teacher performance in MI Ma'arif Kedawung. Support in effective communication, coaching and professional development, motivation, and problem-solving also play a vital role in improving human resources, namely teachers and staff.